2011
DOI: 10.1093/nar/gkr478
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an hepatitis delta virus-like ribozyme at the mRNA 5′-end of the L1Tc retrotransposon from Trypanosoma cruzi

Abstract: L1Tc is a non-LTR LINE element from Trypanosoma cruzi that encodes its transposition machinery and bears an internal promoter. Herewith, we report the identification of an in vitro active hepatitis delta virus-like ribozyme located in the first 77 nt at the 5′-end of the L1Tc mRNA (L1TcRz). The data presented show that L1TcRz has a co-transcriptional function. Using gel-purified uncleaved RNA transcripts, the data presented indicate that the kinetics of the self-cleaving, in a magnesium-dependent reaction, fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 37 publications
(68 reference statements)
2
72
1
Order By: Relevance
“…Cleavage at the R2 5' junction coincides with the cleavage site associated with the ribozymes from other non-LTR retrotransposon clades- R4 (R4 [12]; Dong , Figure 6A), L1 [13], RTE [12]. In this report, analyses of the self-cleavage activity of diverse R2 elements indicated that in most species cleavage is within the 28S rRNA gene from 9 to 36 nt upstream of the R2 5' junction.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Cleavage at the R2 5' junction coincides with the cleavage site associated with the ribozymes from other non-LTR retrotransposon clades- R4 (R4 [12]; Dong , Figure 6A), L1 [13], RTE [12]. In this report, analyses of the self-cleavage activity of diverse R2 elements indicated that in most species cleavage is within the 28S rRNA gene from 9 to 36 nt upstream of the R2 5' junction.…”
Section: Discussionsupporting
confidence: 52%
“…Some elements have been shown to encode a promoter, which initiates RNA synthesis at the precise 5' end of each element, while other elements are suggested to rely on co-transcription with cellular genes. Strong support for the latter was obtained when catalytically active HDV-like ribozymes were found in many non-LTR elements [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first suggestion that 5Ј processing is performed by a ribozyme encoded in the 5Ј UTR of the retrotransposon was proposed when an HDV-like ribozyme was discovered at the 5Ј end of an Anopheles gambiae RTE (5). Subsequent analysis of the Drosophila R2 and Trypanosoma cruzi L1 elements showed that they also harbor HDVlike ribozyme at their 5Ј termini (6,7).…”
mentioning
confidence: 99%
“…In addition, two in-tandem Pr77-hallmarks were found in T. brucei SIDER2 ( Tb SIDER2(126)Rz, Figure 2 and Additional file 1: Table S1) showing a hybrid folding of ribozymes L1 Tc and R2 [23, 25]. No SIDER1 signature was found, either in T. brucei or T. congolense that fitted any folding compatible with an HDV-like ribozyme.…”
Section: Resultsmentioning
confidence: 99%